2007
DOI: 10.1105/tpc.106.042549
|View full text |Cite
|
Sign up to set email alerts
|

Maize Histone Deacetylasehda101Is Involved in Plant Development, Gene Transcription, and Sequence-Specific Modulation of Histone Modification of Genes and Repeats

Abstract: Enzymes catalyzing histone acetylation and deacetylation contribute to the modulation of chromatin structure, thus playing an important role in regulating gene and genome activity. We showed that downregulation and overexpression of the maize (Zea mays) Rpd3-type hda101 histone deacetylase gene induced morphological and developmental defects. Total levels of acetylated histones and histone acetylation of both repetitive and nonrepetitive sequences were affected in hda101 transgenic mutants. However, only trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 62 publications
5
85
0
Order By: Relevance
“…McrBC digests DNA that is methylated at two or more cytosines, thus reducing PCR amplification proportionally to the m C level in the sequence encompassed by the selected primers (Rossi et al, 2007). The results indicated that m C in the promoter of O2 targets and of the azs19.B-1-4 locus was higher in leaves compared with endosperms ( Figure 3).…”
Section: Cytosine Methylation In O2 Target Genesmentioning
confidence: 65%
See 1 more Smart Citation
“…McrBC digests DNA that is methylated at two or more cytosines, thus reducing PCR amplification proportionally to the m C level in the sequence encompassed by the selected primers (Rossi et al, 2007). The results indicated that m C in the promoter of O2 targets and of the azs19.B-1-4 locus was higher in leaves compared with endosperms ( Figure 3).…”
Section: Cytosine Methylation In O2 Target Genesmentioning
confidence: 65%
“…This experiment provided evidence for possible changes in nucleosome occupancy during transcription activation and was also relevant to appropriately correct ChIP data obtained using antibodies against modified histones. Indeed, nucleosome density may not be homogeneous across the genome in different transcriptional states or in mutants affecting histone modifier activity (Ng et al, 2006;Rossi et al, 2007). This implies that nucleosome-rich and nucleosome-poor regions may appear as more and as less modified then they really are, respectively.…”
Section: Analysis Of Nucleosome Density At O2 Target Genesmentioning
confidence: 98%
“…Several physiological outputs of histone deacetylation that are highly relevant for plant biotechnology can be titrated through HDC1 expression, without producing any of the morphological abnormalities observed for manipulation of HDACs in Arabidopsis, rice, and maize (Tian and Chen, 2001;Jang et al, 2003;Zhou et al, 2005;Rossi et al, 2007;Tanaka et al, 2008). Thus, HDC1 opens avenues to exploit epigenetic regulation for crop improvement without risking unwanted side effects caused by interference with fundamental roles of chromatin modifications in tissue differentiation.…”
Section: Hdc1 Still Promotes Growth Under Moderate Drought and Salt Smentioning
confidence: 99%
“…Knockout mutants and RNAi lines of stress-inducible histone deacetylase of Arabidopsisand maize showed increase in histone acetylation accompanied by changes in histone methylation pattern and derepression of silenced genes. 26,27 Thus, dynamic histone modification marks could be converted into DNA methylation marks, which are often more stable.…”
Section: Histone Modificationsmentioning
confidence: 99%